2005
DOI: 10.1590/s0104-530x2005000300006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of technology adoption on mass customization ability of broad and narrow market firms

Abstract: Despite the increasing number of mass customization (MC) studies in the literature and practice, two research gaps still remain. First, there is a lack of empirical studies to test predicted theoretical relationships between MC strategic, technical, and performance aspects (Tu et al., 2001). Second, there is limited understanding about the role of technology, including information technology in MC systems (Åhlström and Westbrook, 1999). This paper investigates the effects of technology adoption on the MC abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Regularentrepreneurtrainingisapanaceatotheundevelopedentrepreneurialcapabilitiesthat characterizegeneralistsratherthanspecialists,dependenceonshort-rangeplanningandreluctance in the use of technology (Dibrell, Davis, & Craig, 2008). In fact, the determination to prosper depends on the entrepreneur hard work and persistence (Silveira & Fogliatto, 2005). Training enhancestheentrepreneurabilitytoadoptnewtechnologyrelevanttobusinessgrowth (Ekpeet al,2016).However,slothfulacceptanceofnewtechnologieshasoccasionedbusinessstart-upsto closewithinfewyearsofoperation.…”
Section: Path Analysismentioning
confidence: 99%
“…Regularentrepreneurtrainingisapanaceatotheundevelopedentrepreneurialcapabilitiesthat characterizegeneralistsratherthanspecialists,dependenceonshort-rangeplanningandreluctance in the use of technology (Dibrell, Davis, & Craig, 2008). In fact, the determination to prosper depends on the entrepreneur hard work and persistence (Silveira & Fogliatto, 2005). Training enhancestheentrepreneurabilitytoadoptnewtechnologyrelevanttobusinessgrowth (Ekpeet al,2016).However,slothfulacceptanceofnewtechnologieshasoccasionedbusinessstart-upsto closewithinfewyearsofoperation.…”
Section: Path Analysismentioning
confidence: 99%
“…The studies show that mass customisation is the core manufacturing paradigm. The studies also showed that the crucial determinant of the successful implementation of mass customisation is the abundant use of Flexible manufacturing Technology (FMT) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The studies show that mass customisation is the core manufacturing paradigm. The studies also showed that the crucial determinant of the successful implementation of mass customisation is the abundant use of Flexible Manufacturing Technology (FMT) [6,7]. Kumar and Desmukh [8] remark that today's customer not only expects quality, reliability and competitive pricing but also customised products with timely delivery, it is desirable that an organisation is as flexible as possible,.…”
Section: Introductionmentioning
confidence: 99%